G.E. Moore on logical possibility - Czarnecki, Tadeusz (Logic and Logical Philosophy, 2004)
Aristotle interprets modalities in a manner consistent with common sense. Necessity, possibility and contingency are modes in which sentences are related to their properties of being true or false. Accordingly, modal sentences concern the actual world. As a sentence becomes true in virtue of its relation to the world, the sentence should firstly be materially true if one is to determine whether it is necessarily or contingently true. A sentence is true if it describes as existing what actually exists and simply cannot be true if its content does not refer to the actual world.